Religious Counseling Dzikir untuk Mengatasi Kecemasan tentang Kematian Pasca Kecelakaan - Agung Tri Prasetia (Jurnal al-Shifa Bimbingan Konseling Islam, 2021)
The anxious feelings suffered by the individual stem from the loss of meaning in life. The problem with this research is how to overcome anxiety about death after an accident. The purpose of this study was to determine the anxiety of death after an accident with religious counseling using remembrance. This study uses a qualitative research method that uses a case study approach with the subject of one accident victim aged 21 years. The instrument in this study was observation, interviews and client related data. The results of this mini research study state that religious counseling using remembrance can change anxiety about death after an accident.